1986
DOI: 10.1007/bf01988001
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H2 receptor activity and histamine metabolism in human U-937 monocyte-like cells and human peripheral monocytes

Abstract: Functional and specific histamine H2 receptors were characterized in human peripheral monocytes and in U-937 cells, before and after retinoic acid--induced differentiation into monocyte/macrophage-like cells. The relative potencies of histamine and the H1, H2 receptor agonists and antagonists studied are remarkably similar in U-937 cells and U-937 monocytes. There is no change in histamine concentration and activity of the enzymes forming and degrading histamine during monocytic-like differentiation. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
2
12
1
Order By: Relevance
“…Finally, the data obtained with separate pretreatment of NK cells or monocytes with raniti dine indicate that NK-regulatory effects of histamine are mediated by a H2 receptor on monocytes, and that H2 receptors on NK effector cells presumably do not participate in the response to histamine. This conclu sion is compatible with the earlier demonstration of functional H2 receptors on human monocytes [27], Earlier studies have demonstrated that monocytes interact with NK cells and thereby regulate their cyto toxic activity. Thus, monocytes produce interferon-a (IFN-a), IL-1, tumor necrosis factor and IL-6, all of which directly or indirectly affect NK cell function [1], Further, monocytes produce prostaglandins, which potently suppress NKCC [28][29][30], By contrast, monocytes recovered after adherence have been re ported to augment NKCC when added to purified NK cells by a mechanism of action which requires cellular proximity and operates independently of sol uble, monocyte-derived factors [28,[31][32][33].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, the data obtained with separate pretreatment of NK cells or monocytes with raniti dine indicate that NK-regulatory effects of histamine are mediated by a H2 receptor on monocytes, and that H2 receptors on NK effector cells presumably do not participate in the response to histamine. This conclu sion is compatible with the earlier demonstration of functional H2 receptors on human monocytes [27], Earlier studies have demonstrated that monocytes interact with NK cells and thereby regulate their cyto toxic activity. Thus, monocytes produce interferon-a (IFN-a), IL-1, tumor necrosis factor and IL-6, all of which directly or indirectly affect NK cell function [1], Further, monocytes produce prostaglandins, which potently suppress NKCC [28][29][30], By contrast, monocytes recovered after adherence have been re ported to augment NKCC when added to purified NK cells by a mechanism of action which requires cellular proximity and operates independently of sol uble, monocyte-derived factors [28,[31][32][33].…”
Section: Discussionsupporting
confidence: 79%
“…Both these substances effectively suppress NKCC in vitro [27][28][29]. By use of the cy clooxygenase inhibitor indomethacin, it was investi gated whether the suppressive effect of IL-2 or the synergistic response to histamine/lL-2 was related to de novo formation of prostaglandins.…”
Section: Role O F Monocyte-derived Cytokines and Cyclooxygenase Productsmentioning
confidence: 99%
“…5C). Moreover, the histamine H1 blocker did not affect the expression of CCL22, whereas the histamine H2 blocker decreased the expression of cell line U937 [16][17][18] , and the regulation of CCL22 was dependent on the presence of H2 receptor in the present study. These result suggest that the effects of histamine on the CCL22 expression are limited in mature macrophages.…”
Section: Concentration Of Ccl22 In the Sera In The Knockout Micecontrasting
confidence: 44%
“…II ,21) Gespach et al 22 ) have shown that the human histiocytic lymphoma cell line U-937, which resembles immature monocytoid cells with monoblast-like characteristics, synthesizes histamine, but that there is no change in HDC activity during monocytic differentiation of the cells. These results indicate that immature monocytoid cells can synthesize histamine.…”
Section: Discussionmentioning
confidence: 99%